The benefit of differential moment concept in managing posterior anchorage and avoiding bite deepening - Harryanto Wijaya; Joko Kusnoto (Universitas Airlangga, 2012)
Background: Anchorage is one of the major concerns in orthodontic space closure. Various methods have been proposed to enhance posterior anchorage in space closure such as headgear, Nance holding appliance, and micro implant as temporary anchorage devices. However, several issues such as patient's compliance, appliance effectiveness, and cost of the device become many clinicians concern. The differential moment concept in segmented arch is a technique that requires no patient compliance but can effectively manage posterior anchorage and avoid bite deepening by careful application of forces and moments. Purpose: The purpose of this case report is to show the use of differential moment concept in segmented arch technique to manage posterior anchorage and to avoid bite deepening. Case: A 21 years old female patient with protrusive teeth as her chief complaint was treated using fixed orthodontic appliance. Case management: The treatment included four first bicuspid extraction and space closure utilizing differential moment concept in segmented arch. Conclusion: It can be concluded that application of differential moment concept in segmented arch technique is a non invasive, compliance independent, effective, and cost efficient method to manage posterior anchorage and to avoid bite deepening. latar belakang: Penjangkaran merupakan salah satu aspek yang sering kali menjadi masalah dalam penutupan ruang pada perawatan ortodonti. Berbagai metode disarankan untuk memperkuat penjangkaran posterior dalam penutupan ruang seperti headgear, piranti penahan Nance, dan implan mikro sebagai alat penjangkar sementara. Namun demikian, beberapa hal seperti kerjasama pasien, efektivitas piranti, dan biaya dari alat-alat tersebut sering menjadi perhatian/pertimbangan bagi klinisi. Konsep momen diferensial pada segmented arch adalah suatu cara yang efektif untuk memperkuat penjangkaran dan menghindari pendalaman gigitan tanpa memerlukan kerjasama pasien. tujuan: Laporan kasus ini bertujuan untuk menunjukkan penggunaan konsep momen diferensial pada segmented arch untuk mengatasi masalah penjangkaran posterior dan pendalaman gigitan. Kasus: Seorang perempuan usia 21 tahun dengan keluhan utama gigi-gigi anterior protrusif dilakukan perawatan dengan alat ortodonti cekat. tatalaksana kasus: Perawatan yang dilakukan meliputi pencabutan 4 premolar pertama dan penutupan ruang dengan konsep momen diferensial pada segmented arch.